Experimental and Mathematical Studies for Optimality of GTAW Parameters on Similar and Dissimilar Steel Substrates - Bandaru Kiran; Dega Nagaraju; Senthil Kumaran Selvaraj; Baye Molla (Advances in Materials Science and Engineering)
Argon arc welding is a frequently used process, to assist various manufacturing processes. The paper highlights the postweld experimental results of similar (EN 10025 Steel-Grade S295) and dissimilar (D36 shipbuilding steel) materials, which possess a wide range of applications in manufacturing industries. In this work, experimental studies are carried out for optimality of gas tungsten arc welding (GTAW) parameters on a butt joint with single and double V 45° groove angles using Taguchi orthogonal L9 array design. The welding is carried out using the back hand technique, and the filler rod is taken as ER303L to obtain finer welded joints. After the weld, residual stresses, microhardness, and geometrical properties of weld are studied at varied zones, that is, weld zone, HAZ, and base metal to examine the weld efficiency with specific predefined weld parameters. Furthermore, tensile tests are carried out for the weldments with optimal predefined weld parameters, and subsequently, the welded specimens with better tensile strength are discussed in the results. Genetic algorithm and mathematical modelling are opted for selecting the final optimal welding parameters. As per the obtained results of residual stresses, hardness, and tensile tests, dissimilar double V groove butt joint is projected to have more effective weld joint.